Lyme Endocarditis as an Emerging Infectious Disease: A Review of the Literature - Nikolić, Aleksandra; Boljević, Darko; Bojić, Milovan; Veljković, Stefan; Vuković, Dragana; Paglietti, Bianca; Micić, Jelena; Rubino, Salvatore (Frontiers in Microbiology, 2020)
Lyme endocarditis is extremely rare manifestation of Lyme disease. The clinical manifestations of Lyme endocarditis are non-specific and can be very challenging diagnosis to make when it is the only manifestation of the disease. Until now, only a few cases where reported. Physicians should keep in mind the possibility of borrelial etiology of endocarditis in endemic areas. Appropriate valve tissue sample should be sent for histopathology, culture, and PCR especially in case of endocarditis of unknown origin PCR on heart valve samples is recommended. With more frequent PCR, Borrelia spp. may be increasingly found as a cause of infective endocarditis. Prompt diagnosis and treatment of Lyme carditis may prevent surgical treatment and pacemaker implantations. Due to climate change and global warming Lyme disease is a growing problem. Rising number of Lyme disease cases we can expect and rising number of Lyme endocarditis.